2011
DOI: 10.1002/bjs.7374
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of the duodenal manifestations of familial adenomatous polyposis

Abstract: Surgery should be reserved for advanced or malignant polyps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 40 publications
0
16
0
4
Order By: Relevance
“…Repeated endoscopic mucosal resection with argon plasma coagulation has recently been used without major complications in selected patients with large duodenal polyps or plaques, resulting in downstaged adenomatosis [10], but large prospective studies are needed to allow a definite evaluation of this treatment option. At present, surgery is therefore the recommended cancer prophylaxis, although endoscopic treatment may be used in selected patients [24].…”
Section: Discussionmentioning
confidence: 99%
“…Repeated endoscopic mucosal resection with argon plasma coagulation has recently been used without major complications in selected patients with large duodenal polyps or plaques, resulting in downstaged adenomatosis [10], but large prospective studies are needed to allow a definite evaluation of this treatment option. At present, surgery is therefore the recommended cancer prophylaxis, although endoscopic treatment may be used in selected patients [24].…”
Section: Discussionmentioning
confidence: 99%
“…Aufgrund des hohen Karzinomrisikos im Spigelman-Stadium IV muss hier ein chirurgisches Vorgehen empfohlen werden, wobei der pankreaserhaltenden Duodenektomie, auch aufgrund der geringeren Morbiditätsrate gegenüber der Pankreatikoduodenektomie der Vorzug zu geben ist [319,320].…”
Section: Level Of Evidence 1cunclassified
“…Most practitioners perform surveillance and remove adenomatous lesions endoscopically, reserving surgery for large lesions or cancer. Parc et al (39) performed a retrospective review of the literature from 1965 to 2009 and reported that recurrence rates did not appear to differ between endoscopic removal and transduodenal resection of duodenal adenomas.…”
Section: Familial Adenomatous Polyposis (Fap)mentioning
confidence: 99%